Athlete-specific analyses of leg joint kinetics during maximum velocity sprint running - Bezodis, I.; Salo, A.; Kerwin, D. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The effect of variations in joint kinetics on sprint performance in individual athletes is not yet known. To investigate biomechanical contributions to maximum velocity sprint running, data were collected from one elite male sprinter performing maximum effort 60 m sprints. High-speed video (200 Hz) and ground reaction force (1000 Hz) data were collected at the 45 m mark. Horizontal velocity and joint kinetics, via inverse dynamics, were calculated for two trials. The velocity of the step was closely linked to step length, knee angular velocity before touchdown, peak-to-peak centre of mass oscillation, hip extension moment during stance and ankle positive work before take-off. The study revealed the potential for athlete-specific, detailed biomechanical analysis and feedback to aid the technical work of athletes and their coaches across a range of sporting skills.